Применение растущих пирамидальных сетей для диагностики финансового состояния металлургического предприятия (Путеводитель предпринимателя, 2020)
The trends in the metallurgical complex of the Russian Federation are considered, the application of growing pyramidal networks algorithms for diagnosis of the financial situation of industrial enterprises is suggested, an example of the use of mathematical tools considered as an element of information security of corporate information system in a metallurgical plant is given.